Tissue‐resident memory T cells in diseases and therapeutic strategies - Daoyuan Xie; Guanting Lu; Gang Mai; Qiuyan Guo; Guofeng Xu (MedComm)
Abstract Tissue‐resident memory T (TRM) cells are crucial components of the immune system that provide rapid, localized responses to recurrent pathogens at mucosal and epithelial barriers. Unlike circulating memory T cells, TRM cells are located within peripheral tissues, and they play vital roles in antiviral, antibacterial, and antitumor immunity. Their unique retention and activation mechanisms, including interactions with local epithelial cells and the expression of adhesion molecules, enable their persistence and immediate functionality in diverse tissues. Recent advances have revealed their important roles in chronic inflammation, autoimmunity, and cancer, illuminating both their protective and their pathogenic potential. This review synthesizes current knowledge on TRM cells’ molecular signatures, maintenance pathways, and functional dynamics across different tissues. We also explore the interactions of TRM cells with other immune cells, such as B cells, macrophages, and dendritic cells, highlighting the complex network that underpins the efficacy of TRM cells in immune surveillance and response. Understanding the nuanced regulation of TRM cells is essential for developing targeted therapeutic strategies, including vaccines and immunotherapies, to enhance their protective roles while mitigating adverse effects. Insights into TRM cells’ biology hold promise for innovative treatments for infectious diseases, cancer, and autoimmune conditions.